Thursday night lights : the story of Black high school football in Texas - Hurd, Michael, 1949- (Jack and Doris Smothers series in Texas history, life, and culture, 2017)
At a time when "Friday night lights" shone only on white high school football games, African American teams across Texas burned up the gridiron on Wednesday and Thursday nights. The segregated high schools in the Prairie View Interscholastic League (the African American counterpart of the University Interscholastic League, which excluded black schools from membership until 1967) created an exciting brand of football that produced hundreds of outstanding players, many of whom became college All-Americans, All-Pros, and Pro Football Hall of Famers, including NFL greats such as "Mean" Joe Green (Temple Dunbar), Otis Taylor (Houston Worthing), Dick "Night Train" Lane (Austin Anderson), Ken Houston (Lufkin Dunbar), and Bubba Smith (Beaumont Charlton-Pollard). Thursday Night Lights tells the inspiring, largely unknown story of African American high school football in Texas. Drawing on interviews, newspaper stories, and memorabilia, Michael Hurd introduces the players, coaches, schools, and towns where African Americans built powerhouse football programs under the PVIL leadership. He covers fifty years (1920-1970) of high school football history, including championship seasons and legendary rivalries such as the annual Turkey Day Classic game between Houston schools Jack Yates and Phillis Wheatley, which drew standing-room-only crowds of up to 40,000, making it the largest prep sports event in postwar America. In telling this story, Hurd explains why the PVIL was necessary, traces its development, and shows how football offered a potent source of pride and ambition in the black community, helping black kids succeed both athletically and educationally in a racist society.